Preoperative Fibrosis-4 (FIB-4) Evaluation May Be Helpful to Evaluate Prognosis of Gastric Cancer Patients Undergoing Operation: A Retrospective Study - Xu, Ke; Shi, Mingming; Zhang, Weiteng; Shi, Yiyi; Dong, Qiantong; Shen, Xian; Chen, Xiaolei; Lin, Ji (Frontiers in Oncology, 2021)
Background Liver dysfunction and chronic inflammation influence the prognosis of many tumors and surgical outcomes. This study was performed to determine whether the Fibrosis-4 (FIB-4) index, originally defined as a noninvasive fibrosis marker, can predict the prognosis of patients with gastric cancer undergoing radical gastric cancer surgery. Methods We have retrospectively analyzed 594 consecutive patients with gastric cancer who underwent gastrectomy in our database. The FIB-4 index was calculated using laboratory data and age before gastrectomy. The clinical utility of FIB-4 was evaluated by X-tile. Patients were divided into two groups (high and low FIB-4 index groups), and their overall survival (OS) was investigated. Cox regression analysis was used to identify the independent parameters associated with prognosis. Finally, we developed a prognostic prediction model by using R statistical software. Results A total of 556 patients, including 422 men and 134 women, were enrolled. Of these, 61 (11.0%) and 495 (89.0%) patients had low and FIB-4 indexes, respectively. In addition to the indicators of FIB-4, preoperative age, tumor site, surgical procedure, TNM stage, and postoperative complications were found to be independent predictors of prognosis (P < 0.05). Among patients, the FIB-4 index group had significantly shorter OS (log-rank P = 0.01) than the low FIB-4 index group. This association was also confirmed in the multivariate analysis (hazard ratio, 4.65; 95% confidence interval, 1.07-4.29; P = 0.031). Conclusions Preoperative FIB-4 index can predict long-term outcomes of gastric cancer patients who had undergone gastrectomy.